Knee Confidence Trajectories Over Eight Years and Factors Associated With Poor Trajectories in Individuals With or at Risk for Knee Osteoarthritis. Issue 11 (16th July 2022) - Chang, Alison H.; Lee, Jungwha (Julia); Almagor, Orit; Chmiel, Joan S.; Hayes, Karen W.; Moisio, Kirsten C.; Sharma, Leena
Abstract : Objective: To identify distinct trajectories of lack of knee confidence over an 8‐year follow‐up period and to examine baseline factors associated with poor trajectories in individuals with or at risk for knee osteoarthritis (OA). Methods: The Osteoarthritis Initiative is a prospective cohort study of individuals with or at high risk for knee OA. Confidence in the knees was assessed within the Knee Injury and Osteoarthritis Outcome Score instrument querying how much the individual is troubled by lack of confidence in his/her knee(s), rated as not‐at‐all (score = 0), mildly (score = 1), moderately (score = 2), severely (score = 3), and extremely (score = 4) troubled, reported annually from baseline to 96 months. Lack of knee confidence was defined as a score of ≥2. We used latent class models to identify subgroups that share similar underlying knee confidence trajectories over an 8‐year period and multivariable multinomial logistic regression models to examine baseline factors associated with poor trajectories. Results: Among 4, 515 participants (mean ± SD age 61.2 ± 9.2 years, mean ± SD BMI 28.6 ± 4.8 kg/m 2 ; 2, 640 [58.5%] women), 4 distinct knee confidence trajectories were identified: persistently good (65.6%); declining (9.1%); poor, improving (13.9%); and persistently poor (11.4%). Baseline predictors associated with persistently poor confidence (reference: persistently good) were younger age, male sex, higher body mass index (BMI), depressive symptoms, more advanced radiographic disease, worse knee pain, weaker knee extensors, history of knee injury and surgery, and reported hip and/or ankle pain. Conclusion: Findings suggest the dynamic nature of self‐reported knee confidence and that addressing modifiable factors (e.g., BMI, knee strength, depressive symptoms, and lower extremity pain) may improve its long‐term course.